Freedom of Marriage for Women Who She Want, Clashes Between Culture And Human Right Law. Lombok, West Nusa Tenggara. Indonesia - Lalu Hendri Nuriskandar (Jatiswara, 2021)
Women are human beings created who are born with human rights. This right is inherent without distinction between men and women. One of the inherent rights is to love and marry. However, it will be a problem if these rights are limited by tradition and parents. That is what happened in Bonjeruk Village, Jonggat District, Central Lombok Regency, West Nusa Tenggara, Indonesia. Women who want to get married must be in accordance with the wishes of their parents, namely at least have a knighthood. Even if their daughters love people who do not have a royal title, they will never be allowed to marry. As a result, many girls are adults but not yet married. Thus, this article aims to find out how Human Rights Law views this matter. By using a descriptive qualitative approach, the writer will try to answer and solve these problems. To support this, the authors use literature review as material to collect data. If it is linked to human rights law, it is a violation of the rights to have children, have a spouse and freedom to choose a life partner. In addition, what is the main barrier is culture, meaning that it is the culture that prevails in the village, and must be obeyed. However, for women it is torture.